Study of deuterium plasma interaction with a tungsten target within RPI-IBIS facility - Skladnik-Sadowska, E.; Malinowski, K.; Sadowski, M.J.; Czaus, K.; Kubkowska, M.; Ladygina, M.S.; Sartowska, B. (Вопросы атомной науки и техники, 2008)
The paper presents results of experimental research on the interaction of a pulsed plasma-ion stream with a tungsten (W) target. The pulsed deuterium plasma was produced within the RPI-IBIS (Multi-Rod Plasma Injector) facility at IPJ in Swierk. Measurements were carried out by means of optical spectroscopy and corpuscular diagnostic techniques. Structural changes in the irradiated targets were investigated with a SEM. Before experiments with the W-target there were determined operational conditions, when clean deuterium plasma streams can be generated. For that purpose a so-called “slow or PID (Plasma Ion Deposition) mode” of the RPI-IBIS operation was chosen. Particular attention was paid to the identification of spectral lines from WI and WII species. The obtained results, i.e. optical spectra and other characteristics have demonstrated applicability of the RPI-IBIS facility for research on the interaction of plasma streams with W-targets, e.g. those constituting some internal parts of fusion facilities.